Model Prediksi Arus Kas di Masa Depan (Studi Empiris pada Perusahaan Telekomunikasi yang Terdaftar di BEI) - Yunita Maharani (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
This study aims to determine future operating cash flows by measuring the independent variables, namely gross profit, operating profit, net income and as additional information for users of the company's financial statements. External companies, especially investors, make this information a consideration in investing. The object of research is a telecommunications company listed on the Indonesia Stock Exchange (BEI) in 2009-2018. Data were analyzed using the EVIEWS 9 program with panel data regression analysis. The results showed that gross profit had a significant negative effect on cash flow, operating profit had a significant positive effect on cash flow, net income had a negative effect on cash flow. Simultaneously, gross profit, operating profit and net income have a negative effect on cash flow.